The experiences of individuals with Multiple Sclerosis in the Western Cape, South Africa - Chrisma Pretorius; Ninon Joubert (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2014)
Background: Multiple Sclerosis (MS) is a debilitating and degenerative lifelong neurological disease that seems to be growing increasingly more prevalent in South Africa. Objectives: The aim of this qualitative study was to explore the personal experiences of individuals with MS in the South African context. The focus of this study was on the challenges faced by individuals with MS, as well as the resources that help them to cope with this debilitating, neurological condition.